2020
DOI: 10.1177/0269215520984133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined home-based, overground robotic-assisted gait training and usual physiotherapy on clinical functional outcomes in people with chronic stroke: A randomized controlled trial

Abstract: Objectives: To assess the effect of a home-based over-ground robotic-assisted gait training program using the AlterG Bionic Leg orthosis on clinical functional outcomes in people with chronic stroke. Design: Randomized controlled trial. Setting: Home. Participants: Thirty-four ambulatory chronic stroke patients who recieve usual physiotherapy. Intervention: Usual physiotherapy plus either (1)10-week over-ground robotic-assisted gait training program ( n = 16), using the device for ⩾30 minutes per day, or (2) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…According to previous studies evaluating the effect of RAGT as an add-on to conventional physiotherapy, patients with (subacute or chronic) stroke exhibited improved ambulation function, lower-extremity motor function, balance, and gait performance both immediately postintervention and at follow-up, and these improvements were superior to those conventional physiotherapy [14,16,17,19,21,22,24,25,33]. By contrast, some studies have shown that training effects in locomotion function, activities of daily living, and gait were not superior to those of conventional stroke training in patients with subacute stroke [15,18,20,23].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…According to previous studies evaluating the effect of RAGT as an add-on to conventional physiotherapy, patients with (subacute or chronic) stroke exhibited improved ambulation function, lower-extremity motor function, balance, and gait performance both immediately postintervention and at follow-up, and these improvements were superior to those conventional physiotherapy [14,16,17,19,21,22,24,25,33]. By contrast, some studies have shown that training effects in locomotion function, activities of daily living, and gait were not superior to those of conventional stroke training in patients with subacute stroke [15,18,20,23].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, several studies have evaluated the effects of RAGT in patients with stroke [20][21][22][23][24][25]. A Cochrane review proposed that RAGT combined with physiotherapy increased gait velocity and odds of participants being able to walk independently [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Robotic devices for in-home walking training: (A) AlterG Bionic Leg ( Wright et al, 2020 ), (B) HAL lower-limb exoskeleton (Anneli Nilsson et al, 2014 ), and (C) SMA ( Buesing et al, 2015 ). …”
Section: Home-based Rehabilitation Systemsmentioning
confidence: 99%
“…The AlterG Bionic Leg ( AlterG, 2015 ; AlterG, n.d ), a portable dynamic battery-operated over-ground wearable lower extremity orthosis, provides adjustable progressive mobility training by supplementing existing muscle strength, providing audio-sensory feedback and mobility assistance during rehabilitation ( Stein et al, 2014 ; Iida et al, 2017 ; Wright et al, 2020 ). This dynamic orthosis supports knee mobility when standing or walking by providing external support to the lower extremity and assisting the patient in aid of weight shifts and knee movement and can be worn in a manner similar to an orthopedic knee brace.…”
Section: Home-based Rehabilitation Systemsmentioning
confidence: 99%